NEP 2020 and Bal Vatika : A Comparative Study of Implementation, Teacher Perspectives, Infrastructure, and Qualitative Dimensions (MSW Management Journal, 2026)
Primary education is considered one of the most crucial stages of the educational continuum, and the National Education Policy 2020 lays down a comprehensive roadmap for the revival and transformation of school education beginning with the Foundational Stage. Recognizing the critical importance of early childhood years, NEP recommends the implementation of multiple strategies in mission mode to strengthen foundational learning across the country. Under NEP 2020, it is mandated that prior to the age of six, every child should attend a “Preparatory Class” or “Bal Vatika” before entering Grade 1. NEP 2020 strongly emphasizes Early Childhood Care and Education (ECCE) as a foundational pillar for lifelong learning and overall development. In this context, the present study entitled “NEP 2020 and Bal Vatika: A Comparative Study of Implementation, Teacher Perspectives, Infrastructure, and Qualitative Dimensions” was undertaken to examine differences in the implementation and effectiveness of Bal Vatikas in Central and State Government schools. A descriptive survey design was employed, and Bal Vatika teachers working at the foundational stage under NEP 2020 from both Central and State Government schools were included in the study. Descriptive statistical tools such as mean scores, frequencies, and percentages were used to analyze the data. The findings revealed that while Bal Vatikas have been moderately successful in implementing play-based learning approaches, several significant challenges persist, including the lack of formal ECCE-specific training for teachers, limited use of play-based activities in certain contexts, inadequate infrastructure, and inconsistencies in curricular implementation.